The dark and light of human nature: Spanish adaptation of the light triad scale and its relationship with psychological well-being - Stavraki, Maria; Artacho-Mata, Edgar; Bajo, Miriam; Díaz, Darío (Current Psychology, 2023)
Against the negative conception of human nature employed by the Dark Triad, another instrument was recently developed to evaluate positive traits, the Light Triad Scale. Our first objective was to apply the same approach of bifactorial models of mental health, which argue that the absence of psychopathology does not necessarily indicate the presence of positive health, to the evaluation of personality. In this sense, we expected that the Light Triad and the Dark Triad are two distinct but interrelated domains of personality, and not just two opposite poles of the same spectrum. Moreover, we examined the relationship of both the Light Triad Scale and the Dark Triad Scale with well-being. To do it, we first adapted this instrument to Spanish and studied its factorial validity, factor invariance for age and gender, and reliability. A total of 1158 participants from Spain completed the Light Triad Scale, the Short Dark Triad Scale and Psychological Well-Being Scales. Confirmatory factor analysis suggested that the Spanish adaptation of the Light Triad Scale showed an adequate fit to the data and scalar invariance across gender and age. Parallel analysis and exploratory factor analysis confirmed the bifactorial model of positive-negative personality traits. Finally, the results showed a positive relation between Light Triad and well-being. The Spanish adaptation of the Light Triad is a useful instrument to assess positive personality traits, independently of the negative personality characteristics assessed by the Dark Triad. In closing, the Light Triad seems to be a core component of positive psychological functioning.
Keywords: dark triad; light triad; measurement; well-being; Scopus; JCR